PENGEMBANGAN INSTRUMEN TES BERBASIS LITERASI SAINS SISWA SMP PADA MATERI GETARAN DAN GELOMBANG - Ramadani, Rizza Dewi; Yennita, Yennita; Ernidawati, Ernidawati (LPPM UNIVERSITAS PGRI SILAMPARI, 2024)
The purpose of this research is to develop test instruments based on aspects of scientific literacy indicators. The type of research used is Research and Development (R&D) research using the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) development model. Validation was carried out by 3 expert lecturers, all assessment indicators for each feasibility aspect were declared valid and in the good or appropriate category. The material aspect obtained an average score of 71.1% (valid), the construction aspect obtained an average score of 77.8% (valid), the scientific literacy aspect obtained an average score of 71.1% (valid) and the grammatical aspect obtained a score average 80% (very valid). This shows that from the material aspect, construction, scientific literacy, and grammar as a whole have a valid level with an average score of 75%. The validity stage of the test items and the reliability of the test instrument after the small group trial phase involved 34 class VIII students of SMP Negeri 10 Tapung. The results of the reliability of the test instrument used the KR 21 formula , which was 0.55 and was in the medium category.